The Effect of Different Steaming Temperatures on Albumin Levels of Scad Fish (Decapterus ruselli) - Fitrawan, M. Dzaky; Shofy Mubarak, Ahmad; yuli pujiastuti, dwi (Journal of Marine and Coastal Science, 2023)
Albumin is a plasma protein that consists of a single polypeptide chain and is used to accelerate the recovery of split/damaged cell tissue. Albumin is produced from human blood in the form of human serum albumin (HSA) which is fulfilled through imports at a relatively expensive price. The alternative albumin is needed to get the cheaper albumin but has the same clinical aspects, such as albumin from the scad fish (Decapterus ruselli). The purpose of this study is to determine the effect of different steaming temperatures on the albumin levels of scad fish (Decapterus ruselli) and get the optimal steaming temperature used to obtain albumin levels from scad fish (Decapterus ruselli). This research was conducted by the Completely Randomized Design (CRD) method which consists of 4 different steaming temperature treatments with 5 replications. The parameters observed were albumin content, protein content, and yield. The parameters were tested using One Way Analysis of Variance (ANOVA) followed by the Duncan Multiple Range Test. The results of this study showed that the treatment of different steaming temperatures had a significant effect (p<0.05) on the albumin levels and percentage of protein content. The optimum steaming temperature to obtain the highest albumin content from scad fish species Decapterus ruselli is 35â„ƒ with an albumin content of 0.1394 g/L. Keywords: Scad fish, steaming, albumin, protein, yield